Implementación del programa 5S en la planta de una pequeña empresa textil de la confección - Heros Callirgos, Maria Fernanda (2021)
This research responds to the problem generated by waste in the production of clothing in small textile companies in Lima. That is, it is proposed to increase productivity from the reduction of excess waste, reprocesses, defectives and keep the job in order, without neglecting safety through the Lean implementation of 5S, which consists of 5 stages: eliminate , order, clean, standardize and discipline. The implementation of the 5s program will bring economic, social and technological benefits to productivity in textile microenterprises, costs will be reduced and continuous improvement will be promoted. Therefore, the results will be measurable through indicators that go hand in hand with the objective of continuous improvement. This work will mainly use secondary sources. The chosen sources are characterized by being related to the main theme, that is, they speak of the implementation of the Lean methodology in the textile sector. The main characteristics they have is that they touch on topics of textile manufacturing, lean methodology, 5S, and that they are not too old to have a good reference. In addition, by comparing indicators, it will seek to expose the reasons for the importance and effectiveness of implementing the 5S Methodology in the textile industry. Some of the results are the reduction of waste, reprocessing and downtime, which lead to a reduction in costs.